Analysis of Factors Affecting the Use of PPE (Personal Protective Equipment) in Nurses on the Prevention of Nosocomial Infections at Bina Kasih Hospital Medan - Suryani, Ade Irma; Asriwati, Asriwati; Nasution, Ramadhani Syafitri (PROMOTOR, 2025)
One of the efforts to provide labor protection for Occupational Safety and Health (K3) in hospitals is by providing Personal Protective Equipment. The purpose of this study is to analyze the factors that affect the use of PPE in Nurses in Bina Kasih Hospital Medan. This type of research includes quantitative research with a cross sectional approach. The population in this study was 152 nurses with a sample of 60 people based on the results of sample calculation using the Slovin formula. Data collection in the study used questionnaires and processed into SPSS with univariate, bivariate and multivariate analysis. The results of the study with the chi square statistical test found that the variables of age, working period, knowledge, attitude, availability of PPE, supervision and social support were related to the p<sig value of α (0.05). Based on the results of the multivariate analysis, it is known that the most dominant variable influences, namely, the attitude variable (p=0.003, Exp(B) 14.931), namely attitude has an influence of 14.9 times on the use of PPE, the working period (p=0.004, Exp(B) 13.169), namely the working period has an influence of 13 times on the use of PPE, and social support (p=0.012 Exp(B) 8.592), namely social support has an influence of 8.5 times on the use of PPE. It can be concluded that the variables of working period, attitude and social support are the factors that most affect nurses in using PPE. It is recommended to Ananda Bekasi Hospital, especially to nurses, to always improve the performance of nursing care provided to patients by paying attention to the completeness of PPE in accordance with the SOPs that have been set by the work agency.